(untitled) - Coakley, Jay J. (Boston, 2004)
The book is the definitive text for the sport sociology course. Taking a global, issues-oriented approach to study the role of sport in society, this text encourages the discussion of current sports-related controversies and helps students develop critical thinking skills.
Anh văn chuyên môn TDTT
Keywords: Sports,Sports,Thể thao; Social aspects,Psychological aspects,Khía cạnh xã hội